Voices and Identity Positionality in EFL Teaching and Learning Policy in an Islamic Bilingual Boarding School in Indonesia - Octavianah, Dian; Putra, Kristian Adi; Sumardi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Students' interactions in school-based activities across subject areas and linguistic groups have been the focus of study on the relationship between identity and learning. Likewise with what happened in the bilingual class which is very interesting to be studied further. Therefore the current study aims to analyze the positionality of students considering the voices of students, subject teachers, and school administrators influenced by school language policies. This study uses case study research. The data were collected out of 102 students that participated in the initial interview, four focal participants were chosen. Two of the students were female, and two were male. Semi-structured interviews and observations were performed. The qualitative content analysis utilizes the gathered data to produce unique representations of the transcripts, such as what is being discussed at a specific time. The findings of this study share students' positive and negative voices toward the implemented language policy at the school. They position themselves as passive and active English users in recognizing their identity positionality. This study may be of relevance to those active in secondary or higher education research, decision-making and advocacy in the non-profit and public sectors, school leadership and governance, and teaching and learning.